Effect of copper in palm kernel meal diet in reproductive system of farm animals - Yaakub, Halimatun; Alimon, Abdul Razak; Ismail, I. (2011)
Studies were conducted to evaluate the effect of PKC on the reproductive system of rabbit, sheep and goat. All animals were fed on diets that contain no PKC (control), PKC or PKC mixed with molybdenum sulphate. In male rabbit, the PKC diet reduced the percentage of spermatogonia, spermatozoa and increased the percentage of degenerated cells. In female rabbit, the PKC diet reduced the number of large follicles (>1.0mm) on the ovaries and reduced the percentage of early morula stage embryos. In sheep, the PKC diet did not change their libido and mating behaviour but numerically increase the percentage of spermatozoa, Sertoli cells and degenerated cells. In goat, the PKC diet did not affect the semen quality, however, histological results shows that the percentage of spermatids, Leydig cells and degenerative cells were altered. In conclusion the Cu content in PKC diets probably affects reproductive organs differently species of animal.